Regenerasi Embriosomatik Tengkawang (Shorea stenoptera Burck.) Pada beberapa Konsentarsi Zat Pengatur Tumbuh GA3 dan BAP ( Somatic Embryos Regeneration of Tengkawang (Shorea stenoptera Burck.) at Various Concentrations of Plant Growth Regulator GA3 and BA - . Neliyati (Bioplantae, 2013)
This research was aimed to indentify the effect of varies type and concentration of plant growth regulators for induce callus embryo somatic regeneration from Tengkawang plantlets. The type of plant growth regulators are GA3 and BAP and the concentration of GA3 are 0.1, 0.5 and 1.0 ppm and BAP are 1.0, 3.0, 5.0 ppm. The result of this experiment showed all treatment could induced the regeneration of callus somatic embryos to form a new root organs but failure to induced shoot formation. The highest percentage of root formation was achieved at plant growth regulator BAP 3.0 ppm. Culture which failure to regenerate the new organ, still induced callus with compact structure and at GA3 treatment the colour. Was dominan with sulfur colour dan brown at BAP treatment..Key word: Tengkawang , growth regulator,regenaration